Revisiting the Theory of Coagulation of Colloidal Dispersions An Improved Expression for the Stability Ratio - Liu, Longcheng (Langmuir : the ACS journal of surfaces and colloids, 2022)
The stability of a colloidal dispersion has long been expressed in terms of the stability ratio. Based on the available theories of coagulation of colloidal dispersions, a novel expression, complying with the classical definition, is developed for the stability ratio. It accounts for the contributions of both primary and secondary minimum coagulations to the overall rate of coagulations. In addition, it can also be regarded as the result of a combination of the kinetic theory of an ideal gas and the Smoluchowski theory with Fuchs' correction, considering the interaction between identical spherical particles and their surfaces immersed in a symmetrical electrolyte solution. The agreement with experimental data suggested that it is superior to the classical ones in describing the weak dependence of the stability ratio on the particle size and the valence of the counterion, by emphasizing the importance of the secondary minimum coagulation in dispersion stability and the complementation between the two modes of coagulation